Aktualisasi Etika Pemasaran di Era Industri 4.0 Dalam Perspektif Al-Qur'an - Uray Januardy; Achmad Abubakar; Hasyim Haddade (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This research sets out from the fact that advances in information technology in the current era or what is known as the industrial era 4.0. has brought major changes to occur in human life in the field of marketing, especially product promotion. The changes referred to include the convenience of business actors in promoting and disseminating product information so that it reaches consumers. However, sometimes marketing activities by business actors are not in accordance with proper ethics, both in terms of legal norms and the Koran values. This study aims to formulate the actualization of marketing ethics in the context and condition of today's society from the perspective of the Koran. This study applies a qualitative approach and belongs to library research. Based on this research, it is obtained that marketing ethics in the industrial era 4.0. currently has a very important position so that businessmen do not arbitrarily use advances in information technology by carrying out various ways that are not in accordance with regulations and the values ​​of the Koran. In addition, the actualization of marketing ethics from the Koran perspective as a response to the industrial era 4.0 can be done by spreading content of promotion based on piety and honesty, displaying sharia-compliant and gharar-less content, incubating local products into marketing management, and orienting the business to the merit goals.